(untitled) (CIPEEX, 2025)
Introduction: Postoperative pain is a common inflammatory response that affects about 80% of patients, with 70% reporting moderate to severe pain. This can delay recovery, impair daily activities, and cause psychological issues. Proper identification and management of pain are crucial to prevent complications, such as chronic pain and physical disability. Additionally, preserving muscle strength (MS) through early mobilization after orthopedic surgeries is essential to avoid complications and prolong rehabilitation. Muscle weakness, hip mobility, and biomechanical behavior are key factors in recovering from lower limb (LL) injuries. Studies indicate that loss of MS may be associated with pain intensity and plays an important role in postoperative rehabilitation. Objective: The study aimed to analyze the association between pain and muscle weakness in patients in the immediate postoperative period of LL surgery at a reference hospital in the central-northern region of Goiás. Methodology: This was a cross-sectional study with quantitative data analysis conducted on 92 volunteers, following approval by the Research Ethics Committee. Participants, of both sexes, aged between 18 and 60, underwent orthopedic surgeries on LL due to fractures or ligament injuries. Those with low consciousness or polytrauma were excluded. Muscle strength was evaluated using manual muscle tests, graded on a scale from 0 to 5, where 5 indicated normal strength. Pain was measured using the Visual Analog Scale (VAS), widely used in clinical research. Participants were divided into two groups: those without muscle weakness (MS ≥ 25) and those with muscle weakness (MS < 25). Statistical analysis was performed using relative and absolute frequencies, and the independent t-test was used to compare group means. Results: The average age of participants was 39.18 years, with 68.5% being male and 31.5% female. Of the 92 volunteers, 46.9% showed muscle weakness, with a total strength score ≤ 24 according to the Medical Research Council (MRC) scale. The group with muscle weakness had an average age of 41.23 years, while the group without weakness had an average of 37.69 years, though this difference was not statistically significant. Regarding pain, the group with muscle weakness had a mean VAS score of 1.513, while the group without weakness had a score of 1.453, with no significant difference between them (p = 0.658). Conclusion: The findings of this study suggest that muscle weakness is common in the immediate postoperative period of orthopedic surgeries on LL, regardless of the reported pain intensity. Although pain did not differ significantly between groups with and without muscle weakness, MS should be considered a crucial factor in the rehabilitation of these patients. Future studies should investigate this interaction more deeply and explore strategies that can improve muscle strength, enhancing postoperative recovery and quality of life.